the sum of pth term of ap isq andqth term of ap is p find [p+q]th term of ap
Answers
Answered by
5
Refer to the attachment for your solution
Hope it helps!
Hope it helps!
Attachments:
![](https://hi-static.z-dn.net/files/db7/239bc72e085e17417ecd7d774f397ddf.jpg)
![](https://hi-static.z-dn.net/files/dc9/1d9cf02fbf86e9d2ba898535d53aafce.jpg)
sonalmishra:
it is wrong
Answered by
2
Here your answer goes
Given ,
P th term of an AP = q
q th term of an AP = P
To Find :-
[ p + q ] th term of an AP
Solution :-
We know that ,
Formula for
So , For pth term =
⇒ q = a + ( P - 1 ) * d ------->>>> 1
Similarly ,
⇒ P = a + ( q - 1 ) * d ---------->>>> 2
From (1) and (2)
⇒ d ( p -q ) = - ( p - q )
⇒ d = -1
Substitute the value of d in equation (1)
q = a + ( P - 1 ) * d
⇒ q = a + ( p - 1 ) * (-1)
⇒ q = a - p + 1
⇒ a = q + p - 1
⇒ a ( p + q ) = a + ( n - 1 ) * d
⇒ a (p + q - 1 - p - q + 1 )
⇒ a [ p + q ] = 0
Therefore , [ p + q ] th term of an AP = 0
↓↓↓↓↓
Be Brainly
Together WE go far
Attachments:
![](https://hi-static.z-dn.net/files/d31/9193e45fd4e4417f3198fe5a68e9d0b6.jpg)
Similar questions